1979
DOI: 10.1017/s0305000900007698
|View full text |Cite
|
Sign up to set email alerts
|

Some facts on negation: Wode's four-stage developmental theory of negation revisited

Abstract: According to Wode (1977), the development of negation in children's speech goes through four stages.1 Stage I consists of one-word negation, i.e. children using a single nein, 'no', to express negation. Stage II consists of two-word negation, which is developmentally further divided into 11a for anaphoric negation and 116 for non-anaphoric negation. In the former, nein is used correctly in its proper grammatical function, but in the latter, nein stands for adult nicht 'not'. Stage III consists of intrasententi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

1985
1985
2003
2003

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…No, that is a tapir) (Wode, 1977;Park, 1977 ;Pea, 1980). The first general change is the production of increasingly sophisticated functions from simple refusals around 1;0 (e.g.…”
Section: The Development Of Negationmentioning
confidence: 99%
See 1 more Smart Citation
“…No, that is a tapir) (Wode, 1977;Park, 1977 ;Pea, 1980). The first general change is the production of increasingly sophisticated functions from simple refusals around 1;0 (e.g.…”
Section: The Development Of Negationmentioning
confidence: 99%
“…Is that a horse ? No, that is a tapir) (Wode, 1977;Park, 1977 ;Pea, 1980). However, because Bloom (1970) provided evidence for multiple functions at early ages, this change may reflect differences in the frequency of use for any given function rather than evidence for the acquisition of new functions.…”
Section: The Development Of Negationmentioning
confidence: 99%
“…Based on these and some further research, Wode (1977: 100) suggested three universal stages in the development of negative structures which can be summarized as in (9). There has been some controversy with respect to IIa and IIb; see Park (1979) and Clahsen (1983). Since I am not concerned with anaphoric negation, this is not relevant.…”
Section: The Syntax Of Negation In First Language Developmentmentioning
confidence: 99%
“…As for German, the development of the syntax of negation is also reasonably well studied; see, for example, Wode (1977), Park (1979), Clahsen (1983;1988a), Mills (1985) and Meisel (1997). Once again, one finds that NEG is first placed externally.…”
Section: The Syntax Of Negation In First Language Developmentmentioning
confidence: 99%